DESIGN AND DEVELOPMENT OF ROBLOX-BASED CRAFTEDU BLOX FOR CONSTRUCTING AND DECOMPOSING CUBE STRUCTURES - Ahmad Rijal Hakim Fathulloh; Nuriana Rachmani Dewi (Universitas Muhammadiyah Metro, 2026)
Mathematics learning on cube geometry in elementary schools still faces challenges, particularly in students’ conceptual understanding and spatial visualization abilities. These challenges are influenced by the limited use of learning media that primarily rely on two-dimensional representations, restricting opportunities for conceptual exploration. This study aimed to (1) design Roblox-based CraftEdu Blox digital learning media for teaching the construction and decomposition of cube structures and (2) determine the validity and feasibility of the developed media through expert evaluation. The study employed a Research and Development (R&D) approach using the ADDIE model limited to the analysis, design, and development stages. The participants were 54 sixth-grade students at SD Negeri Palebon 03. Data were collected through observations, interviews, initial ability tests, and expert validation instruments. The results indicated that CraftEdu Blox was successfully developed as a three-dimensional virtual learning environment that supports conceptual exploration through direct interaction with geometric objects, structured navigation, and interactive learning and assessment features. Expert validation results showed feasibility percentages of 94.00% for language, 95.38% for material, and 93.85% for media aspects, all categorized as highly feasible. These findings indicate that Roblox-based CraftEdu Blox is highly suitable for elementary mathematics learning and has the potential to support students’ conceptual understanding and spatial visualization in constructing and decomposing cube structures. Pembelajaran matematika pada materi geometri kubus di sekolah dasar masih menghadapi berbagai tantangan, terutama pada pemahaman konsep dan kemampuan visualisasi spasial siswa. Tantangan tersebut dipengaruhi oleh keterbatasan penggunaan media pembelajaran yang masih didominasi representasi dua dimensi sehingga membatasi kesempatan siswa untuk melakukan eksplorasi konsep secara mendalam. Penelitian ini bertujuan untuk (1) merancang media pembelajaran digital CraftEdu Blox berbasis Roblox pada materi mengonstruksi dan mengurai bangun kubus serta (2) mengetahui validitas dan kelayakan media yang dikembangkan melalui penilaian para ahli. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model ADDIE yang dibatasi pada tahap analisis, desain, dan pengembangan. Subjek penelitian terdiri atas 54 siswa kelas VI SD Negeri Palebon 03. Pengumpulan data dilakukan melalui observasi, wawancara, tes kemampuan awal, dan instrumen validasi ahli. Hasil penelitian menunjukkan bahwa CraftEdu Blox berhasil dikembangkan sebagai lingkungan belajar virtual tiga dimensi yang mendukung eksplorasi konsep melalui interaksi langsung dengan objek geometri, navigasi yang terstruktur, serta fitur pembelajaran dan evaluasi yang interaktif. Hasil validasi ahli menunjukkan persentase kelayakan sebesar 94,00% pada aspek bahasa, 95,38% pada aspek materi, dan 93,85% pada aspek media, yang seluruhnya berada dalam kategori sangat layak. Temuan ini menunjukkan bahwa CraftEdu Blox berbasis Roblox sangat layak digunakan dalam pembelajaran matematika sekolah dasar dan berpotensi mendukung pemahaman konsep serta kemampuan visualisasi spasial siswa pada materi mengonstruksi dan mengurai bangun kubus.